The effectiveness of mergers as a strategy to create and sustain competitive advantage: a case of Chevron hotel - Mhlanga, Tobias (Midlands State University, 2018)
Most researches on mergers have concentrated on mergers as a tool to improve financial performance, shareholders value and as a way to gain access on new markets. This study seeks to analyse the effectiveness of mergers as a strategy to create and sustain competitive advantages. In 2012 Chevron Hotel and Flamboyant Hotel merged and the motives behind the merger were the creation of economies of scale, cost synergies, effective management of interdependence and strengthening of the capital intensity. However in the post merger era the entity witnessed an increase in costs and a decrease in revenues that impacted negatively on the financial performance. In the study a descriptive research design was used in data collection and primary data was collected through questionnaires and interviews. The population samples comprising of thirty nine employees were drawn from Chevron Hotel and the judgemental sampling technique was used to come up with a sample. The study unveiled that the entity is enjoying some competitive advantages through the acquisition of highly technical machines , increase in market power, gaining of purchasing power through discounts and charging of low prices. The challenges faced by the hotel include a decline in financial performance, lack of communication and coordination amongst its departments. Recommendations were suggested and they include the implementation of programmes that facilitate knowledge and skills sharing amongst employees and offering a variety of services to cater for the ever changing customer tastes and preferences.